Pauvreté et politique sociale : le bilan des années Bush - Taoufik Djebali (Revue LISA)
Nine days after he was sworn in, Bush launched his social program, the Faith-Based Initiatives (FBI), a major component of his “compassionate conservatism.” The FBI constituted a break with the Reagan monetarist tradition, even if they are motivated by the withdrawal of the State and the reduction of the social budget. The role of the FBI is to help charities, in particular religious organizations, to invest more in social work. On the whole, the social policy implemented during the Bush years is evaluated negatively. Poverty increased rapidly and the financial promises in favor of the Faith-Based Organizations were not kept. Worse, new revelations have been disclosed. The Bush administration is accused of having used the FBI and public money to make political gains and set up an obscure funding system that benefited the Republicans and their political allies.